Pengaruh Kualitas Layanan Check-In terhadap Kepuasan Penumpang Jeju Air di Bandara Bali - Ni Kadek Pari Iswari; R. Ibnu Haitam (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Since the lifting of the pandemic status, Indonesia’s aviation industry has experienced significant growth, marked by a rise in both domestic and international passengers. Bali, particularly I Gusti Ngurah Rai International Airport, has emerged as a major destination, with a 22% increase in total passengers between 2023 and 2024. Jeju Air is one of the international airlines that recently launched a route to Bali, making service quality crucial, especially in ground handling activities like the check-in process. This research investigates the impact of check-in counter personnel service quality on the satisfaction of Jeju Air passengers at I Gusti Ngurah Rai International Airport. Conducted between May 1st and 30th, the study employed a quantitative method using simple linear regression analysis. Data were collected, analyzed, presented, and concluded systematically. The theoretical framework combines the Servqual model of service quality (Zeithaml et al.) and passenger satisfaction theory by Kotler. Results show a positive influence of service quality on satisfaction, evidenced by a t-value (5.776) exceeding the t-table value (2.425), thus supporting the alternative hypothesis. The coefficient of determination (R²) is 0.254, indicating that 25.4% of the variation in passenger satisfaction is explained by the quality of check-in counter services.